EFISIENSI PENGGUNAAN FAKTOR PRODUKSI DAN PENDAPATAN USAHATANI TUMPANGSARI STROBERI-BAWANG DAUN DI DESA SERANG KECAMATAN KARANGREJA KABUPATEN PURBALINGGA - Savira Kusumadewi; Djeimy Kusnaman; Irene Kartika Eka Wijayanti (JSEP (Journal of Social and Agricultural Economics), 2021)
Strawberry (Fragaria sp.) is a type of fruit that has high economic value. An to increase the income of strawberry farmers is by intercropping with leek. To understand the efficiency of the farming the by using production input. This research aims to 1) analyze the effect of the use of production factors, 2) analyze the level of efficiency in the use of production factors, and 3) to analyze the profit level of intercropping strawberries-leek in Serang Village, Karangreja District, Purbalingga Regency. There are 35 samples obtained using simple random sampling. The analysis was performed using the Cobb Douglass production function analysis, the NPM / BKM ratio and farm income analysis. The results of this research were the use of production factors, seed; area; labor; and insecticides partially affected the production of intercropping strawberries, while the production factors of chicken-husk fertilizer; NPK-Phonska fertilizer; other fertilizers; and fungicides had no effect on the production of intercropping strawberries. The production factors for seeds; labor; and insecticides have an NPM-BKM ratio value greater than one where the use of these inputs is not efficient. Meanwhile, the production factor for land area has an NPM-BKM ratio value of less than one where the use of these inputs is not efficient. R / C for cash costs was 4.61 and R / C for total costs was 1.09. The R / C value for both cash costs and total costs has a value greater than one, so the strawberry and leek intercropping farming in Serang Village can be said to be profitable.